Application of the linear perturbation theory to compressible flow about bodies of revolution - Young, A. D.; Kirkby, S. (College of Aeronautics, Cranfield, 1947)
The linearised theory is developed in some detail in order to clarify the differences between two-dimensional and axi-symmetric flow. In agreement with other authors it is concluded that the perturbation velocity on a thin body of revolution in compressible flow is 1/β2 times the perturbation velocity in incompressible flow on a thinner body at reduced incidence obtained by reducing the lateral dimensions of the original body in the ratio (3:1). This result is applied to a representative family of streamline bodies of revolution at zero incidence. Continues…